Giant Inverse Barocaloric Effect of Ferroelectric Salts Driven by Negative Thermal Expansion - Yin Dai; Menghao Wu (Advanced Physics Research)
Abstract Refrigeration technologies based on the barocaloric effect have garnered significant attention, while their potential applications are limited by the poor performance of current materials. Here it is proposed that ferroelectric ionic salts with covalent‐like bondings like LiI may become ideal candidates. The pressure‐induced phase transition between two phases with distinct densities and entropies leads to tremendous negative thermal expansion (with volume reduced by 13%) and inverse barocaloric effect, which are facilitated by the low transition barriers due to the long‐range Coulomb interaction. Using ab initio‐based training database, we trained the machine learning potential of LiI based on a deep neutral network‐based mode, and this simulations of its barocaloric effect reveal a high entropy change and thermal conductivity, and in particular, the estimated adiabatic temperature change, pressure sensitivity and relative cooling power are all unprecedented. This prediction provides a high‐performance barocaloric mechanism for practical applications and also expands the scope of barocaloric materials to simple and facile binary salts.